Peningkatan Kemandirian Lansia Melalui Okupasi Terapi dan Group Psychotheraphy di PSTW Sabai Nan Aluih Sicincin Padang Pariaman - Sunardi Sunardi; Renidayati Renidayati (Jurnal Sehat Mandiri, 2020)
The increasing number of the elderly causes complex problems for the elderly, families and communities. Physiological and psychological changes make the elderly feel useless, experience decreased motivation and independence. One of the efforts to increase the independence of the elderly in order to remain qualified is the application of therapeutic modalities in the form of occupational therapy and group psychotherapy. This study aims to determine the changes in the independence of the elderly before and after Ocupasi therapy and Group Psychotherapy at PSTW Sabai Nan Aluih Sic Cincin, Padang Pariaman Regency. The study used a quantitative approach with "Quasi Experimental pre and post test with control group which was held from March to November 2019. The study sample was 63 elderly people who were taken by purposive sampling." The research instrument used the Katz AD Index. Data analysis used Paired sample t-test and Independent t test. The increase in the average independence of the dementia elderly was greater in the elderly who were given Ocupasi therapy and Group Psychotherapy by 18.83 compared to those who received Ocupasi therapy of 7,121. Conclusion The elderly who received occupational therapy and group psychotherapy experienced an increase in independence compared to the elderly who only received occupational therapy. It is recommended that nursing home nurses receive occupational therapy training modified with group psychotherapy and that the training module needs to be improved.